Regulating Artificial Intelligence : An Ethical Approach - Teo, Yi-Ling (2018)
As the use of artificial intelligence (AI) becomes more pervasive in everyday life, questions are being asked about where the legal and ethical bright lines are – or should be – in regulating its use.